Kajian Artikel: Evaluasi Faktor-Faktor yang Mempengaruhi Waktu Tunggu Pelayanan Resep Rawat Jalan Rumah Sakit di Indonesia Tahun 2023: Review Article: Evaluation of Factors Affecting Waiting Times for Hospital Outpatient Prescription Services in Indonesia 2023: Systematic Review - Sagita, Vina A.; Sukmadryani, Yunilah; Sanjaya, Suwitno (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Pharmaceutical Care are one of the services that must be provided in a hospital. The indicator used to measure good pharmaceutical service is the waiting time for prescription drug services. Prescription services that have fast service waiting times will increase patient satisfaction with overall pharmaceutical services. Initial search results for related articles still show waiting times for drug prescriptions that do not meet the minimum service standards at hospitals. The aim of this research is to determine and evaluate the factors that influence the waiting time for outpatient prescription services in hospitals. The research uses related literature studies and produces descriptive data. Based on an article research regarding factors that influence waiting times for hospital drug prescription services in Indonesia in 2021-2023, namely human resources in pharmacy installations, completeness of patient files, availability of drugs prescribed by doctors, use of electronic and manual prescriptions together, compounded drug prescriptions, information systems in pharmacy installations, doctors who are difficult to contact to confirm prescriptions, inadequate room space. Hospitals need to pay attention to these factors so that the quality of waiting time for pharmaceutical services in hospitals can be maintained.